2011
DOI: 10.1179/107902610x12883422813660
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health among persons with spinal cord injury: What is the role of physical ability?

Abstract: Objectives: Self-rated health (SRH) is a powerful concept that has greatly advanced our understanding of health and health outcomes. The SRH measure has become increasingly common in health research. Yet, puzzles remain about what shapes SRH ratings. The absence of knowledge is particularly acute in the context of disability. The aim of this study was to examine the relationship between SRH and self-rated physical ability in a sample of individuals with spinal cord injury (SCI). Methods: Data from 140 eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This coincides with a study conducted by Machacova, et al, about the health and physical functioning of people with spinal cord injury [9]. Erosa, et al, by contrast found that people with spinal cord injury for whom severe functional disorders have been defined do not always evaluate their overall health status as being bad.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This coincides with a study conducted by Machacova, et al, about the health and physical functioning of people with spinal cord injury [9]. Erosa, et al, by contrast found that people with spinal cord injury for whom severe functional disorders have been defined do not always evaluate their overall health status as being bad.…”
Section: Discussionsupporting
confidence: 48%
“…Functional self-evaluation differs from expected functional limitations and physical abilities, as was noted in Machacova, et al [9]. Functional abilities must be seen in the context of functional self-evaluation, which can be affected and influenced by a variety of individual barriers and opportunities that are faced by respondents on an everyday basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many studies have previously shown an association between particular dimensions of disability and perceived health, in samples of patients with particular diseases. For instance, social functioning is an important determinant of perceived health among heart failure patients [40] while physical ability has an important role on perceived health among spinal cord injury patients [41]. And for individuals with major depressive episode, cognition and embarrassment seem to be more relevant disability dimensions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Responses were reverse scored for easier interpretation in this study. The use of a single item to assess self‐rated health has revealed clinically and theoretically consistent results among respondents with SCI (Krahn, Suzuki, & Horner‐Johnson, ; Machacova, Lysack, & Neufeld, ).…”
Section: Methodsmentioning
confidence: 99%